Pelaksanaan Cakupan Kelas Balita Terhadap Pencapaian Standar Pelayanan Minimal (SPM) Pelayanan Kesehatan Balita di Puskesmas Bekawan - Rahimah Rahimah; Riski Novera Yenita; Jufenti Ade Fitri; Dilgu Meri (Pelantar Press, 2025)
Bekawan Public Health Center, as one of the primary health service centers in Indragiri Hilir Regency, plays a strategic role in the implementation of toddler classes. Based on the preliminary study conducted on March 3, 2025, data was obtained showing that the number of toddlers aged 0-59 months in the working area of Bekawan Public Health Center is 220 individuals. The number of toddler classes available is 10 toddler classes spread across 5 villages. The goal of this research is to determine if there is an effect of the implementation of toddler class coverage on the achievement of minimum service standards (SPM) for toddler health services at Bekawan Public Health Center. This type of research is a correlation quantitative study with a cross-sectional study approach, conducted from February to July 2025. The population in this study includes all toddlers (0-59 months) registered in the working area of Bekawan Public Health Center and attending toddler classes. The sample in this study consists of 13 registered toddlers (0-59 months).